Insane Offenders, Dangerous Criminals, Criminal Responsibility and Security Measures: The Positivist Criminology Network and the Reform of Criminal Law in Imperial Germany - Härter, Karl (GLOSSAE. European Journal of Legal History, 2023)
The chapter studies the concept of the ‘insane offender’ from the angle of the positivist criminology network that formed around Franz von Liszt and the International Union of Penal Law and investigates its effect on the reform of criminal law in imperial Germany. The influence of criminological positivism on penal reform will be analyzed from the historical perspective of intertwined national and international arenas of positivist criminology and forensic psychology that produced criminological normativity and influenced attempts to change the German penal code. A main focus is on the major figure of German positivist criminology and the International Union of Criminal Law: Franz von Liszt, who served as an intellectual focal point in the formation of the concepts of ‘insane offenders’, ‘dangerous criminals’ and ‘security measures’ and who partly transformed them into juridical categories that were to serve the ideas of positivist criminology. Franz von Liszt and the positivist criminology network discussed the relation between insane and dangerous/habitual offenders and, more generally, between mental illness and crime with the intention to implement the resulting concepts and categories into criminal law. This chapter outlines these discussions on diminished criminal responsibility and related security measures and discusses to which extent they were rejected or integrated into the reform of the German penal code.